Analysis of student’s progress in INTEGROVANOY ENVIRONMENT TRAINING COURSE «Algorithmization BASICS and programming» - Nabit Ю.Б. (Journal of Information Technologies in Education (ITE), 2009)
The state of progress of students is analysed after the modules «Library of tasks» and «Current control» at the study of course of «Basis of algorithming and programming». Found out possibilities for the improvement of level of quality of knowledges of students.